Proposals for Second Five Year Plan Government of Madhya Bharat Co-operation Department - Planning Commission (Planning Commission, 1955)
At the end of the Flan period i.e. 1955-56, the position of the Cooperative Movement in the State will not be unsatisfactory and as compared to other State, it would not be found too backward. In fact, it can favourably be compared with the condition of the Cooperative Movement in many of the Fart a States the recommendations of the Rural Credit Survey Report have changed the entire aspect of the Cooperative Movement, so far as it relates to agricultural population which is to be saved from chronic, indebtedness and heavy burden of interest and provided funds for agricultural operations, land improvements and means for better production and marketing.
Government of Madhya Bharat, Co-operation Department